Coronavirus social norms registration - Elena Martinescu; Terence Daniel Dores Cruz (Open Science Framework, 2022)
The main of the current study is to exploratively describe how people perceive, communicate, and enforce novel norms related to Coronavirus. Specifically, we will investigate the following sociual norms: hand hygiene, social distancing, social isolation, and mask wearing.
Keywords: Social and Behavioral Sciences